Treatment for postoperative wound pain in gynecologic laparoscopic surgery: topical lidocaine patches - Kwon, Yong-Soon; Kim, Jong Bun; Jung, Hyun Ju; Koo, Yu-Jin; Lee, In-Ho; Im, Kyung-Teck; Woo, Joon Suk; Im, Kyong Shil (Journal of laparoendoscopic & advanced surgical techniques. Part A, 2012)
This article reports our early experience with the use of lidocaine patches for pain control in the immediate postoperative period after laparoscopic gynecologic surgery. A prospective, double-blind, placebo-controlled clinical trial was conducted on 40 patients undergoing a gynecologic laparoscopy who were randomized to receive either topical patches of 700 mg of lidocaine (n=20) or placebo patches (n=20). The patch was divided evenly into four smaller patches, which were applied at the four port sites and changed every 12 hours for 36 hours after surgery. Postoperative pain was evaluated using the visual analog scale (VAS) score and the Prince Henry and 5-point verbal rating pain scale (VRS), and the analgesic requirement was also evaluated at 1, 6, 12, 24, and 36 hours after surgery. The VAS score for wound pain was lower in the lidocaine patch group at 1 and 6 hours after surgery than the control group (P=.005 and <.0005, respectively). The VAS scores for postoperative pain were lower in the lidocaine patch group at rest 1 hour after surgery (P=.045). The 5-point VRS score for postoperative pain was lower in the lidocaine patch group at 6 and 12 hours after surgery (P=.015 and .035, respectively) than in the control group. Topical lidocaine patches at the laparoscopic port sites reduced postoperative pain, particularly postoperative wound pain after gynecological laparoscopic procedures.